A novel dynamic proteomics approach for the measurement of broiler chicken protein fractional synthesis rate. (17th March 2023) - Peinado‐Izaguerri, Jorge; Zarzuela, Eduardo; McLaughlin, Mark; Small, Alexandra C.; Riva, Francesca; McKeegan, Dorothy E. F.; Bain, Maureen; Muñoz, Javier; Bhide, Mangesh; Preston, Tom
Abstract : Rationale: The study of protein synthesis in farm animals is uncommon despite its potential to increase knowledge about metabolism and discover new biomarkers of health and growth status. The present study describes a novel dynamic proteomics approach for the measurement of protein fractional synthesis rate (FSR) in broiler chickens. Methods: Chickens received a 10 g/kg oral dose of 2 H2 O at day 21 of their life. Body water 2 H abundance was measured in plasma samples using a portable Fourier transform infrared spectrometer. Free and protein‐bound amino acids (AAs) were isolated and had their 2 H enrichment measured by gas chromatography with mass spectrometry (GC/MS). Peptide 2 H enrichment was measured by proteomics analysis of plasma and muscle samples. Albumin, fibrinogen and muscle protein FSR were calculated from GC/MS and proteomics data. Results: Ala appeared to be more enriched at the site of protein synthesis than in the AA free pools. Glu was found to be the AA closest to isotopic equilibrium between the different AA pools. Glu was used as an anchor to calculate n (AA) values necessary for chicken protein FSR calculation in dynamic proteomics studies. FSR values calculated using proteomics data and GC/MS data showed good agreement as evidenced by a Bland–Altman residual plot. Conclusions: A new dynamic proteomics approach for the measurement of broiler chicken individual protein FSR based on the administration of a single 2 H2 O oral bolus has been developed and validated. The proposed approach could facilitate new immunological and nutritional studies on free‐living animals.